The Effect of Attitude of FKM UMJ Students on The Use of Paid Plastic Bags in 2021 - Allan Bahya Zahran; Atika Sari; Almairah Nurfauziah; Denita Nur Anisya; Munaya Fauziah (Muhammadiyah International Public Health and Medicine Proceeding, 2021)
Plastic, particularly plastic bags, is an object that cannot be separated from everyday life. Plastic bags can be used as a wrapper and to transport luggage or groceries, among other things. The use of plastic bags is out of control as a result of the practice of giving them out for free. As a result, better management is required to limit the usage of plastic bags, one of which is the establishment of a paid plastic bag policy. The goal of this study was to see how FKM UMJ students' opinions influenced their use of paid plastic bags in 2021. In June 2021, a qualitative investigation was done as part of this research. In-depth interviews and document reviews were used to acquire data. Purposive sampling was used to choose students from the FKM UMJ Class of 2019 as informants for this investigation. Based on the research that has been done, it is found that the influence of the attitude of FKM UMJ students towards the use of paid plastic bags is positive and supports government policies regarding this matter. So it's time for us to take wise steps in using single-use plastic bags.